Topics of Qur’an Sciences In The Interpretation Of Al- Gorani - Al-Dosky, Mohammad; Al-Atrushi, Ezzedine (Humanities Journal of University of Zakho, 2022)
Sheikh Al-Gorani is one of the Kurdish commentators who served the Holy Qur’an. In this research, we tried to study the topics of the sciences of the Qur’an in its interpretation, and the sciences of the Qur’an are importan matters for those who address the task of interpreting the Holy Qur’an. And among the topics that Sheikh Al-Gurani touched upon in his interpretation is the revelation, and it is the only means that connects the earth to the sky, and it is God’s informing of one of his prophets،And it has three forms: inspiration as it happened to the mother of Musa, a dream as it happened to Abraham, peace be upon him, and revelation to the messengers to speak or send the angel as happened with all the messengers, and the Qur’an revealed to Muhammad, may God bless him and grant him peace, was revealed on the Night of Decree to the House of Glory in the heavens of the world. Then God revealed it to His Messenger as a astrologer in twenty-three years, The wisdom of astrology is to establish the heart of the Messenger of God with it, to keep pace with events and gradualism in the call and legislation, and in the gradual revelation of the Qur’an, a miraculous and additional challenge to the polytheists. And the most correct one in the first thing that was revealed is Surat Al-Alaq, and the last that was revealed is the verse of the Most High Almighty saying: